MODERNITAS DAN GLOBALISASI: TANTANGAN BAGI PERADABAN ISLAM - muhammad rusydi (TAJDID: Jurnal Ilmu Ushuluddin, 2018)
This paper aims to explain the globalization and modernity inpact problem for Islamic civilization. Rennassaince that has been developing in west and has been giving inpact not only for progressing science and technology but also for modernity acceleration in a veriety of life field. But, the progress not for Islam because it has been facing the internal problem such as stupidity and destitution. So that, the conditions have given inpact for Islam that has been more inferior than west. The globalization and modernity moslem civilization was changed by the western civilization. Makalah ini bertujuan untuk membahas tentang dampak modernitas dan globalisasi bagi peradaban Islam. Renaissans yang membawa kepada kemajuan di Barat bukan hanya membawa kemajuan dalam bidang ilmu pengetahuan dan teknologi tetapi juga memunculkan berbagai kemudahan dalam berbagai bidang kehidupan. Maka muncul modernitas dan globalisasi. Namun modernitas dan globalisasi ini tidak banyak menguntungkan Islam dan kaum muslim karena membawa ekses negatif dalam kalangan internal mereka. Bahkan, modernitas dan globalisasi ini menjadi tantangan bagi peradaban Islam dan kaum muslim.